Effects of Environmental Stressors on the Hematological Indices of Some Freshwater Teleosts - Lopez, Nellie (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 2 (1992), 2007)
Changes in blood values were observed in young adult freshwater fishes exposed to environmental stressors. Clarias batrachus (TL=221-391 mm; 68.7-371.4 g) starved for 34, 47 and 53 days showed significant reductions in lymphocyte counts. Lymphocyte percentages decreased while neutrophil percentages increased in starved fish. Oreochromis niloticus (TL=105-172 mm; 19.1-77.6 g) exposed for 30 days to 10 and 20 ppm ZnSO 4 concentrations at pH 6.7-7.2 showed consistent reductions in total WBC and lymphocyte counts but insignificant changes in RBC-related values. O. niloticus (TL=56-124 mm; 4.0-21.7 g) exposed for 96 h to 10, 20, and 30 ppm ZnSO 4 concentrations showed a general tendency of reduction in RBC-reIated values and total and relative WBC counts. Exposure of O. niloticus (TL=56-106mm; 2.9-14.2 g) for 96 h to 5, 10, and 20 ppm ZnSO 4 at low ph (ph 3.1-3.8) elicited marked increases in neutrophil counts and reductions in lymphocyte and RBC counts. O. niloticus (TL=94-154 mm; 13.2-54.4 g) subjected to 24 h and 48 h crowding showed increased hematocrit, neutrophilia, and lymphopenia. In Ophicephalus striatus (TL=259-306 mm; 123.2-192.8 g) stressful effects of crowding and handling were less evident from the blood values obtained after 24 hand 48 h exposure.